Perpustakaan sebagai media pembelajaran mahasiswa - hsapril hsapril (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
This paper aims to understand the basis of the classification applied epistemic first library catalog China, the seven epitomes (Qilue). Design / methodology / approach - Derived from the theoretical attitude that puts knowledge in social enterprise organizations, this study applies a multifaceted framework related to five categories of textual data: seven epitomes; biographical information on the Liuxin k and inteleasifikasi relevant Keywords: Epistemics